Single-Cell Trajectory Inference Guided Enhancement of Thyroid Maturation In Vitro Using TGF-Beta Inhibition - Romitti, Mírian; Eski, Sema Elif; Fonseca, Barbara Faria; Gillotay, Pierre; Singh, Sumeet Pal; Costagliola, Sabine (Frontiers in Endocrinology, 2021)
The thyroid gland regulates metabolism and growth via secretion of thyroid hormones by thyroid follicular cells (TFCs). Loss of TFCs, by cellular dysfunction, autoimmune destruction or surgical resection, underlies hypothyroidism. Recovery of thyroid hormone levels by transplantation of mature TFCs derived from stem cells in vitro holds great therapeutic promise. However, the utilization of in vitro derived tissue for regenerative medicine is restricted by the efficiency of differentiation protocols to generate mature organoids. Here, to improve the differentiation efficiency for thyroid organoids, we utilized single-cell RNA-Seq to chart the molecular steps undertaken by individual cells during the in vitro transformation of mouse embryonic stem cells to TFCs. Our single-cell atlas of mouse organoid systematically and comprehensively identifies, for the first time, the cell types generated during production of thyroid organoids. Using pseudotime analysis, we identify TGF-beta as a negative regulator of thyroid maturation in vitro. Using pharmacological inhibition of TGF-beta pathway, we improve the level of thyroid maturation, in particular the induction of Nis expression. This in turn, leads to an enhancement of iodide organification in vitro, suggesting functional improvement of the thyroid organoid. Our study highlights the potential of single-cell molecular characterization in understanding and improving thyroid maturation and paves the way for identification of therapeutic targets against thyroid disorders.